The Fluvial Reworking of Late Pleistocene Drift, Squamish River Drainage Basin, Southwestern British Colombia - Brooks, Gregory (Géographie physique et Quaternaire, 1994)
ABSTRACTReworked glacial sediment(s) (RGS) represents the component of paraglacial sedimentation derived from the fluvial reworking of late Pleistocene glacial deposits in the postglacial landscape. In Squamish River drainage basin, southwestern British Columbia, the primary source of the RGS transferred to Squamish Valley is fluvial incision into valley-fill deposits in the five major tributary valleys of the watershed. The total volume of RGS transferred to Squamish Valley is 415 x 106m3. The volume of RGS from the individual tributary valleys range from 6 to 130 x 106m3 with valley morphology and late Quaternary history being the important controls upon the specific amount. Geomorphic evidence indicates that the bulk of the RGS was contributed to Squamish Valley thousands of years ago. The transfer of RGS continues at a very low residual rate in the contemporary landscape. RGS appear to represent a minor portion of the Squamish valley-fill and a small component of the postglacial sediments stored in Squamish Valley.